OPACITY FLUCTUATIONS IN THE INTERSTELLAR MEDIUM AT HIGH GALACTIC LATITUDES - POVEDA, ARCADIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1964)
Investigations of the spatial distribution of galaxies by Neyman, Scott and Shane are based on the simplifying assumption that the regions in the sky covered by their work are free from irregular galactic absorption, attributing the observed deviations fr
BOL OBS TONAN TACUB
Keywords: OPACITY FLUCTUATIONS, INTERSTELLAR MEDIUM, HIGH, GALACTIC LATITUDES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS